Fluorescence Microscopy-Based Quantitation of GLUT4 Translocation: High Throughput or High Content? - Stadlbauer, Verena (Int J Mol Sci, 2020)
Due to the global rise of type 2 diabetes mellitus (T2DM) in combination with insulin resistance, novel compounds to efficiently treat this pandemic disease are needed. Screening for compounds that induce the translocation of glucose transporter 4 (GLUT4) from the intracellular compartments to the plasma membrane in insulin-sensitive tissues is an innovative strategy. Here, we compared the applicability of three fluorescence microscopy-based assays optimized for the quantitation of GLUT4 translocation in simple cell systems. An objective-type scanning total internal reflection fluorescence (TIRF) microscopy approach was shown to have high sensitivity but only moderate throughput. Therefore, we implemented a prism-type TIR reader for the simultaneous analysis of large cell populations grown in adapted microtiter plates. This approach was found to be high throughput and have sufficient sensitivity for the characterization of insulin mimetic compounds in live cells. Finally, we applied confocal microscopy to giant plasma membrane vesicles (GPMVs) formed from GLUT4-expressing cells. While this assay has only limited throughput, it offers the advantage of being less sensitive to insulin mimetic compounds with high autofluorescence. In summary, the combined implementation of different fluorescence microscopy-based approaches enables the quantitation of GLUT4 translocation with high throughput and high content.